A Randomized Controlled Trial to Compare the Analgesic Efficacy of Ultrasound-Guided Fascia Iliaca Compartment Block and Femoral Nerve Block in Patients with Neck of Femur Fracture - Josna M. Fernandes; Shruti N. Rathi; Abhay G. Sancheti; Shweta A. Puntambekar; Varshali M. Keniya (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Background and Aims: Regional nerve blocks under ultrasound guidance have heralded the era toward safer anesthetic practices. They provide adequate analgesia during positioning for subarachnoid block in patients posted for hip. We aimed to compare the analgesic efficacy of fascia iliaca compartment block and femoral nerve block for pain during sitting position for subarachnoid block, duration of post-op analgesia, and document any complications. Material and Methods: A randomized double-blind study was conducted in 60 patients undergoing isolated neck of femur fracture surgery under subarachnoid block. They were randomized by a computer-generated randomization table into two groups – group A received a fascia iliaca compartment block and group B received a femoral nerve block. Numeric rating score (NRS) was noted before block, during positioning, and postoperatively for 24 hours. An independent sample t-test and a paired t-test were used for intergroup and intra-group comparisons. Results: The mean NRS before block in group A (7.57 ± 0.50) and group B (7.40 ± 0.49) (P-value = 0.203) was not significant. NRS during positioning in group A (2.10 ± 0.88) was significantly lower than group B (3.33 ± 0.71) (P-value = 0.001*). The mean NRS from the sixth till 20th hour postoperatively was significantly higher in group B compared to group A (P-value <0.05 for all). The mean time to first rescue analgesia was significantly longer in group A (23.57 ± 2.22 hours) compared to group B (11.97 ± 1.73 hours) (P-value = 0.001*). No complications were noted during the study. Conclusion: Fascia iliaca compartment block gives significantly better pain relief during positioning for subarachnoid block and prolonged postoperative analgesia as compared to femoral nerve block.